Political Organising and Mobilising in the Age of the Fourth Industrial Revolution: A Reflection on the Gauteng Young Communist League of South Africa - Kgabo Morifi (The Thinker)
What does the Fourth Industrial Revolution (4IR) portend for the future of political organising and mobilising? As “a way of describing the blurring of boundaries between the physical, digital, and biological worlds...a fusion of advances in artificial intelligence, robotics, the Internet of Things, 3D printing, genetic engineering, quantum computing, and other technologies…” (McGinnis, 2018), the 4IR is primarily concerned with the inchoate transformation of the production of goods and services, resulting from the application of a new wave of technological innovations. Definitions such as these cement the narrow idea that the 4IR is principally about industry, when in reality it is a revolution that goes beyond economic activity concerned with the manufacturing of goods and services.